High‐Precision Barium Isotope Measurements of Carbonates by MC‐ICP‐MS. Issue 2 (8th February 2019) - Zeng, Zhen; Li, Xiaohua; Liu, Yi; Huang, Fang; Yu, Hui‐Min
Abstract : This study presents a high‐precision method to measure barium (Ba) isotope compositions of international carbonate reference materials and natural carbonates. Barium was purified using chromatographic columns filled with cation exchange resin (AG50W‐X12, 200–400 mesh). Barium isotopes were measured by MC‐ICP‐MS, using a 135 Ba– 136 Ba double‐spike to correct mass‐dependent fractionation during purification and instrumental measurement. The precision and accuracy were monitored by measuring Ba isotope compositions of the reference material JCp‐1 (coral) and a synthetic solution obtained by mixing NIST SRM 3104a with other matrix elements. The mean δ 137/134 Ba values of JCp‐1 and the synthetic solution relative to NIST SRM 3104a were 0.21 ± 0.03‰ (2 s, n  =   16) and 0.02 ± 0.03‰ (2 s, n  =   6), respectively. Replicate measurements of NIST SRM 915b, COQ‐1, natural coral and stalagmite samples gave average δ 137/134 Ba values of 0.10 ± 0.04‰ (2 s, n  =   18), 0.08 ± 0.04‰ (2 s, n  =   20), 0.27 ± 0.04‰ (2 s, n  =   16) and 0.04 ± 0.03‰ (2 s, n  =   20), respectively. Barium mass fractions and Ba isotopes of subsamples drilled from one stalagmite profile were also measured. Although Ba mass fractions varied significantly along the profile, Ba isotope signatures were homogeneous, indicating that Ba isotope compositions of stalagmites could be a potential tool (in addition to Ba mass fractions) to constrain the source of Ba in carbonate rocks and minerals. Key Points: A high‐precision method to measure the barium isotope composition of carbonates. The intermediate measurement precision over 12 months was ± 0.04% (2 s ) for δ 137/134 Ba. The barium isotope composition of several carbonate and carbonatite reference materials was measured for interlaboratory comparison.